UPAYA INDONESIA TERHADAP UNESCO DALAM MENJADIKAN PANTUN SEBAGAI WARISAN BUDAYA DUNIA - Haninda, Frizkha; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The Smallholder Oil Palm Rejuvenation Program is a government program in collaboration with oil palm-based companies in Indonesia with the hope of helping the economy of independent smallholders who often experience problems with low oil palm productivity. Kandis Subdistrict is one of the oil palm producing areas that has welcomed the PSR program quite well. However, the community has other problems which are considered to be the source of problems in accelerating the implementation of the people's Oil Palm Rejuvenation program. This study aims to determine how the credibility of the persuader, the channels used, the effects of persuasive communication and the barriers to persuasive communication of Sinarmas.This study used a qualitative research method with a descriptive approach. This research was conducted in the District of Kandis. The research subjects consisted of nine (9) informants who were selected through purposive sampling technique. While the research data were obtained through the process of interviewing, observation and documentation. While the data analysis techniques used were data collection, data reduction, data presentation and conclusion and verification. To achieve data validity, the authors used participatory extension and triangulation.The results showed the credibility of the persuader in showing expertise and trust by using a kinship approach and showing it directly during the planting process as is usually done by the core company. Demonstrating good ethics and attitudes will also give a deep impression to the persuadee. Furthermore, there are two persuasive communication messages, namely verbal (clarity and accuracy) and nonverbal (attributes and gestures of the body and voice intonation). In this study the team used personal channels such as in-person or face-to-face socialization, using agent programs to accelerate the dissemination of information about PSR. The next way is to use mass media such as printed media, namely banners, brochures and pamphlets, as well as online media (internet). Furthermore, the effects are divided into three, namely, the cognition effect that is informative for the farming community, then the affective effect is in the form of a feeling of interest in the PSR program after knowing it, the last is the most expected conation effect, namely when the community decides to register their land on the PSR.Keywords: Persuasive communication, PSR, Sinarmas.